2001
DOI: 10.1161/hy1101.092971
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II via Activation of Type 1 Receptor Upregulates Expression of Endoglin in Human Coronary Artery Endothelial Cells

Abstract: Abstract-Transforming growth factor-␤1 and its subtype receptor endoglin are key components in angiogenesis. We explored the role of angiotensin (Ang) II in the expression of endoglin and the underlying intracellular signaling mechanism in human coronary artery endothelial cells. Incubation of cells with Ang II upregulated endoglin expression in a concentration-and time-dependent manner (maximal effect with 10 Ϫ6 mol/L Ang II at 24 hours). The Ang II type 1 receptor blocker losartan, but not the type 2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Recently, it has been reported that angiotensin II induces endoglin overexpression in cultured endothelial cells. 35 Previous studies have demonstrated that angiotensin II increases TGF-␤1 synthesis in fibroblasts, smooth muscle cells, and renal mesangial cells. 36,37 Angiotensin II also induced the expression of TGF-␤ type I and type II receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that angiotensin II induces endoglin overexpression in cultured endothelial cells. 35 Previous studies have demonstrated that angiotensin II increases TGF-␤1 synthesis in fibroblasts, smooth muscle cells, and renal mesangial cells. 36,37 Angiotensin II also induced the expression of TGF-␤ type I and type II receptors.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Ox-LDL has also been shown to upregulate angiotensin II type 1 receptors in atherosclerosis. 4 Angiotensin II type 1 receptor expression, like ox-LDL, decreases TGF-␤ 1 synthesis and increases the expression of its receptors, 40 and may contribute to alterations in TGF-␤ 1 and its receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences as well as length of mRNA products for endoglin were taken from Li et al, 21 for ␤-3 integrin from GenBank (GenBank accession nos. G26607, M25108), and for ␤-globin from Smith et al 22 All primer pairs were synthesized by Invitrogen (Carlsbad, CA).…”
Section: Determination Of Enos Mrnamentioning
confidence: 99%